2013
DOI: 10.1063/1.4807758
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of bilayer manganite PrCa2Mn2O7 showing charge/orbital ordering

Abstract: The microstructure of the charge/orbital ordering Ruddleden-Popper phase PrCa 2 Mn 2 O 7 was studied by transmission electron microscopy along both the [001] and the [110] orientation. Three coexisting charge/orbital ordering phases CO1, CO2, and CO3 were observed along the [001] orientation at room temperature. Different from the one-dimensional modulation in the CO1 and CO2 phase, the CO3 phase is characterized by two sets of mutually perpendicular structural modulations. From [110] high angle annular da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…1 and Ca (≈71%) is mainly located at the rock-salt layer denoted as Ca(Pr)2 site in the same figure. This atomic distribution is in agreement with previous electron microscopy studies [17,19]. In this structure there are also two positions for the apical oxygens, O1 and O2.…”
Section: B Symmetry Mode Analysis For the High Temperature Disordered...supporting
confidence: 92%
See 2 more Smart Citations
“…1 and Ca (≈71%) is mainly located at the rock-salt layer denoted as Ca(Pr)2 site in the same figure. This atomic distribution is in agreement with previous electron microscopy studies [17,19]. In this structure there are also two positions for the apical oxygens, O1 and O2.…”
Section: B Symmetry Mode Analysis For the High Temperature Disordered...supporting
confidence: 92%
“…1). Further heating leads to an intensity decrease of (2, 3/2, 0) peak until it disappears at TCO1≈360 K. The coexistence of CO1 and CO2 phases has been observed previously [17,18,[35][36][37] and some authors have proposed the occurrence of an intermediate phase with two modulations or a propagation vector k'= (½, ½, 0) [17,18].…”
Section: Results Data Analysis and Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In general, the spatial locations of the chemical dopants are random, which generates a certain kind of disorder in the system. For CMR mangnanites, it has been shown that the ordering of chemical dopants, or the cation ordering has strong influence on the physical properties for both bulk11121314151617 and superlattice structures181920212223242526. However, very few work has dealt the correlation between cation ordering and the electronic phase separation (EPS)27, despite of the fact that EPS is important for both understanding the mechanism of strong electronic correlation and for tuning the physical properties.…”
mentioning
confidence: 99%
“…Our recent TEM study also demonstrated the complexity of the crystal structure and phase transition of this compound. 19,20 Therefore, it is necessary to reinvestigate the crystal and magnetic structures of the series Pr(Sr 1Ày Ca y ) 2 Mn 2 O 7 .…”
Section: Introductionmentioning
confidence: 99%